Discover tai chi for beginners [videorecording (DVD)] - Cole, Scott, 1962- (Scott Cole wellness series., 2007)
"Follow Scott through a seamless journey of healing Chi Kung exercises and easy-to-follow Tai Chi postures designed to open up energy channels, improve breathing and posture, strengthen your core and leg base, and inspire you to move gracefully like a tree in the breeze!"--Container